Gen Z: The Interaction Between Accounting Understanding and Factors Influencing AI Adoption in Accounting Software - Hakim, Muhammad Haekal Fadhillah; Indriasih, Dewi; Astutie, Yanti Puji (Jurnal Sains Sosio Humaniora, 2026)
This study examines the effects of accounting digitalization, prospective accountants' technology readiness, and financial reporting accuracy on the adoption of Artificial Intelligence (AI) in accounting software, with accounting understanding positioned as a moderating variable. The study was motivated by inconsistent findings in prior research regarding the technological and individual factors that drive AI adoption among accounting students, and by the absence of an integrated model linking digitalization, readiness, information quality, and accounting competence. A quantitative survey method was employed, collecting primary data through a structured Likert-scale questionnaire distributed to 400 active accounting students from five higher-education institutions in Tegal City, Indonesia, selected through purposive sampling based on the Slovin formula. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS Statistics 22. The results show that accounting digitalization, technology readiness, and financial reporting accuracy each have a positive and significant effect on AI adoption. Accounting understanding was found to significantly moderate the relationship between accounting digitalization and AI adoption, although in a negative (weakening) direction, while it did not significantly moderate the relationships between technology readiness or financial reporting accuracy and AI adoption. These findings extend the Technology Acceptance Model by clarifying the boundary conditions under which accounting competence shapes technology adoption behavior among future accountants, and offer practical implications for accounting curriculum development and accounting-software design.